PERAMALAN JUMLAH KASUS PENYAKIT CORONAVIRUS DISEASE 2019 DENGAN METODE ARIMA DAN METODE SIR - Iftitahur Rohmah; Mursyidul Ibad (LPPM Universitas Bina Bangsa, 2022)
Almost all parts of the country in the world have experienicng the sama health problem that is Covid 19. Tha spread of Covid 19 increasing every day, in the province of East Java Covid 19 cases are also high with a CFR value 7,44%. It is currently unknown when the Covid 19 pandemic will end, therefore forecasting is needed to predict the spread of Covid 19 in the future. The purpose of this research is to analyze the results of the comparison between the results of forecasting the number of Covid 19 cases using the ARIMA and SIR methods with actual data in July 2021. This research uses forecasting with the method of ARIMA and SIR. Including the type of non-reactive research thah uses daily data on the number of cases of Coronavirus Disease 2019 in East Java from March to June 2021. Data obtained from website https://covid19.go.id/peta-sebaran in the provinceof East Java. Research of forecasting Covid 19 by ARIMA method is the best model which is qualified ARIMA (2,1,2) with the MSE value 0,05 which indicate that the number of cases of Covid 19 disease in July 2021 is increasing. Research of forecasting Covid 19 by SIR create the value R₀ 1,757 so R₀ >1 which indicate that the number of cases of Covid 19 disease has decreased in July 2021